2006
DOI: 10.1086/500212
|View full text |Cite
|
Sign up to set email alerts
|

Posaconazole Is Effective as Salvage Therapy in Zygomycosis: A Retrospective Summary of 91 Cases

Abstract: To evaluate the activity of posaconazole for treatment of zygomycosis, a disease for which therapeutic options are limited, we conducted a retrospective study including 91 patients with zygomycosis (proven zygomycosis, 69 patients; probable zygomycosis, 22 patients). Patients had infection that was refractory to prior antifungal treatment (n=81) or were intolerant of such treatment (n=10) and participated in the compassionate-use posaconazole (800 mg/day) program. The rate of success (i.e., either complete or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
347
0
10

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 581 publications
(363 citation statements)
references
References 17 publications
6
347
0
10
Order By: Relevance
“…Nevertheless, even with aggressive therapy, the rate of mortality is often above 50% (4, 6). It is clear that new strategies for the treatment of zygomycosis are urgently needed.Posaconazole (POS) is a new broad-spectrum triazole with activity against many filamentous fungal pathogens, including zygomycetes (3,8,11,13,14). Experimental infection models and clinical data showed that POS might be useful for the treatment of zygomycosis (3,11,14).…”
mentioning
confidence: 99%
“…Nevertheless, even with aggressive therapy, the rate of mortality is often above 50% (4, 6). It is clear that new strategies for the treatment of zygomycosis are urgently needed.Posaconazole (POS) is a new broad-spectrum triazole with activity against many filamentous fungal pathogens, including zygomycetes (3,8,11,13,14). Experimental infection models and clinical data showed that POS might be useful for the treatment of zygomycosis (3,11,14).…”
mentioning
confidence: 99%
“…8 In a retrospective series of invasive mucormycosis, posaconazole therapy was successful in 60% of subjects with diabetes mellitus, and its overall success rate was 65% in those with pulmonary mucormycosis. 9 Despite motivation and pursuance, our patient could not continue posaconazole beyond 4 weeks because of cost. However, we ensured macroscopic clearance of the mass in repeat bronchoscopy 2 weeks after discontinuation of posaconazole, and he did not develop any symptoms of relapse until 1 month ago.…”
Section: Discussionmentioning
confidence: 90%
“…Newer drugs have been introduced namely: posaconazole, isuvaconzole and echinocandins. While posaconazole has shown promising outcomes, Amphotericin B remains the first-line drug with posaconazole used as a salvage therapy (17). However, it has been proven that management of mucormycosis is multi-modal with surgical management and treatment of the underlying condition as important in antifungal therapy.…”
Section: Case Reportmentioning
confidence: 99%